The visible reflectance spectrum stability and water content resistivity of natural dye coating paint film consisting chlorophyll - Usop, Rohida; Sulaiman, L.; Mazni, N.A.; Manah, N.S.A.; Anuar, Nordiyanah; Arof, Abdul Kariem; Abidin, Zul Hazrin Zainal (Emerald, 2018)
Purpose: The purpose of this paper is to study the colour stability and water content resistivity of the green colour coating paint film (consisting of chlorophyll) during exposure to ultraviolet A (UV-A). Design/methodology/approach: The natural green dye was prepared by immersing Cassia alata L. leaves in absolute ethanol. The extract was prepared in two batches of dye samples where one of it was a pure dye and the other was added with 3 Wt. % Cu(NO3)2 as an additive. Polymer blend as a binder was prepared by mixing poly(methyl methacrylate) (PMMA) and commercial acrylic polyol. The blended polymer was mixed with the natural dye in a specific ratio and applied as coating paint film on glass panel surfaces. The visible spectrum stability (colour stability) and water content resistivity of the coating paint films during exposure to UV-A were monitored. Findings: Addition of Cu(NO3)2 had improved the colour stability of the coating paint film. Fourier transform infrared spectroscopy analysis showed that both coating paint films do not absorb water and are resistive to water content. Research limitations/implications: The ability of Cu(NO3)2 as an colour stability additive to the natural green dye applied in the coating paint film. Practical implications: The coating paint film developed in this work is suitable to be applied on glass substrates. Originality/value: The colour stability of the coating paint film was analysed by using the reflectance spectrum.